Glacier changes in the semi-arid Huasco Valley, Chile, between 1986 and 2016 - Heß, Katharina; Schmidt, Susanne; Nüsser, Marcus; Zang, Carina; Dame, Juliane (Geosciences, 2020)
In the semi-arid and arid regions of the Chilean Andes, meltwater from the cryosphere is a key resource for the local economy and population. In this setting, climate change and economic activities foster water scarcity and resource conflicts. The study presents a detailed glacier and rock glacier inventory for the Huasco valley (28-29° S) in northern Chile based on a multi-temporal remote sensing approach. The results indicate a glacier-covered area of 16.35 ± 3.06 km2 (n = 167) and, additionally, 50 rock glaciers covering an area of about 8.6 km2 in 2016. About 81% of the ice-bodies are smaller than 0.1 km2, and only four glaciers are larger than 1 km2. The change analysis reveals a more or less stable period between 1986 and 2000 and a drastic decline in the glacier-covered area by about 35% between 2000 and 2016. The detailed assessment of six subregions indicates a more pronounced glacier decrease in the vicinity of the Pascua Lama mining project.
Gesehen am 21.07.2022